Rethinking Socrates: Notes On Some Recent Studies - de Luise, Fulvia (Peitho. Examina Antiqua, 2011)
[ Livio Rossetti, Le dialogue socratique, Les Belles Lettres, Paris 2011 e Livio Rossetti, Alessandro Stavru (a cura di), Socratica 2008, Atti Convegno Napoli 2008, Le Rane, Levante, Bari 2011. ]